Implentasi Kebijakan Dalam Menanggulangi Illegal Fishing Atau Iuu Fishing di Indonesia dan Malaysia - Sri Wulan Febriani; Haura Atthahara (Jurnal Ilmiah Wahana Pendidikan, 2022)
Indonesia is one of the archipelagic countries whose entire territory is waters. The issue of sovereignty began to emerge when countries in the world agreed on international maritime law (United Nations Convention on the Law of the Sea, UNCLOS) in 1982 and has been in force since 1994. A problem that is more often polemic is the existence of large and sophisticated fishing vessels. technology originating from outside the two countries is illegally catching fish in the seas of Indonesia and Malaysia. Internationally, illegal fishing is known as Illegal, Unreported, and Unregulated (IUU) Fishing. This study aims to examine maritime policy between Indonesia and Malaysia. To understand the policy that will be taken, the next part of this research is to describe cooperative maritime policy as an analytical framework to assess between Indonesia and Malaysia as a coastal country in handling IUU fishing. This study uses a literature study research method with a qualitative descriptive research approach. The results of the research are the Indonesian government's policy in tackling Illegal Fishing or also IUU Fishing as said by the Ministry of Maritime Affairs and Fisheries by taking one policy, namely by acting decisively for cases of illegal fishing or illegal fishing by sinking foreign ships that stole the fish. Likewise, Malaysia's response to illegal fishing or IUU fishing using Malaysia's MCS operations is planned and funded in a way that maximizes the ability to deal with IUU fishing through cooperation among all maritime enforcement agencies.